EVALUASI PROGRAM PEMBINAAN BAHASA ARAB DI SDIT SWASTA DAFA BINJAI: PENDEKATAN MODEL CIPP - Syaukani; Sri Wahyuni Daulay; Salisa Afany; Sabila Aghnia Fawwaz; Zulfahmi Mar'i; Nurul Huda Zulfiani; Ahmad Fauzan Shidiq; Sultan Kemala Agung; Ahmad Fuadi Fauzi; Iin Febrina Lubis (STKIP Subang, 2026)
This study evaluates the Arabic language development program at SDIT Swasta Dafa Binjai, which is applied as the daily communication language within the school environment. Considering that Arabic plays an important role in Islamic education, its implementation often faces challenges such as lack of consistency, limited vocabulary, and environmental support factors. The study uses the CIPP (Context, Input, Process, Product) evaluation model to measure the success of the program. The evaluation results provide a comprehensive picture, from the alignment of objectives (context), resource readiness (input), implementation and obstacles (process), to the achievement of students' speaking competencies (product). These findings are expected to serve as a reference for improving the curriculum and teaching strategies for maharah al-kalam in the future.